PENGAWASAN OTORITAS JASA KEUANGAN DAN DAMPAKNYA TERHADAP EFEKTIVITAS PERLINDUNGAN DATA KONSUMEN BANK PEREKONOMIAN RAKYAT DI BATAM - Joan Lyne Diyanatalia; Lu Sudirman; Hari Sutra Disemadi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study aims to analyze the implementation of the Financial Services Authority (OJK) supervision of Bank Perekonomian Rakyat (BPR) in protecting consumer data in Batam City. In the context of increasing cases of customer data leaks, this study analyzes the role of OJK in maintaining the confidentiality of customer personal data in accordance with applicable laws. The method used is an empirical legal research method with a sociological and legislative approach. Data were collected through interviews with OJK Riau Islands, BPR Dana Nusantara, and BPR Danamas Simpan Pinjam, as well as literature studies. The results of the study indicate that OJK supervision contributes significantly to increasing BPR compliance with data protection standards, reducing the risk of violations, and building public trust in financial institutions. However, the effectiveness of supervision still faces obstacles, especially related to the limited number of supervisors compared to the number of BPRs that must be supervised. This study is expected to provide insight for consumers and authorities regarding the importance of data protection and encourage transparency in the financial services sector.